2017
DOI: 10.3390/w9110819
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Dynamics of Potentially Toxic Cyanobacteria in the Riverine Region of a Temperate Estuarine System Altered by Weirs

Abstract: Abstract:The effects of weirs on fish and other biological communities have garnered considerable study, whereas the effects of weirs on community composition of toxic cyanobacteria have not yet been well documented. In this study, temporal and spatial variations in species composition and the abundance of potentially toxic cyanobacteria were investigated in the riverine regions of the temperate Youngsan River estuary, where two weirs have recently been constructed. Four stations were sampled 0.5 m below the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…These conditions favored Cyanophyta, rather than Chlorophyta, species diversity at 22°C. Considering that the impact is species-specific, previously reported data regarding the role of winter conditions in a harsh eutrophic environment are inconsistent (Malazarte et al, 2017). The current study indicated the great ability of Chlorophyta and Cyanophyta to tolerate a wide temperature range, forming monospecific and/or multispecific dense blooms in no particular season.…”
Section: Discussionmentioning
confidence: 47%
“…These conditions favored Cyanophyta, rather than Chlorophyta, species diversity at 22°C. Considering that the impact is species-specific, previously reported data regarding the role of winter conditions in a harsh eutrophic environment are inconsistent (Malazarte et al, 2017). The current study indicated the great ability of Chlorophyta and Cyanophyta to tolerate a wide temperature range, forming monospecific and/or multispecific dense blooms in no particular season.…”
Section: Discussionmentioning
confidence: 47%
“…In other studies, before and after weir construction, native shes were more sensitive to disturbance than exotic species in RRHSs (Jo et al, 2019), and riverine wetlands used as habitats and refuge for zooplankton also decreased (Im et al, 2020). A cyanobacteria community, a phytoplankton community, was also shown to be affected by weir construction (Malazarte et al, 2017).…”
Section: Introductionmentioning
confidence: 74%
“…Weirs are lateral structures installed on rivers that change the running water ecosystem into a lentic ecosystem (becoming an RRHS) and hinder water ow, which is a core process of the river ecosystem, thus changing the structure of the food webs (Jo et al, 2019). Environmental changes and community changes induced by 4LRPs have been investigated in many studies (Malazarte et al, 2017;Jo et al, 2019;Im et al, 2020). However, there are few studies on the deterioration of the connection between zooplankton communities induced by 4LRPs.…”
Section: Introductionmentioning
confidence: 99%